ВИБОРЧІ ПРОЦЕДУРИ ЯК СКЛАДОВА ВИБОРЧОГО ПРОЦЕСУ - Ільницький, Михайло Степанович (SUPREMANCE OF LAW, 2018)
In the article, on the basis of analysis, it is argued that the use of information technologies on the example of such electoral procedures as voting and counting and establishing election results indicates a number of positive features for the electoral process. This is, in particular, an increase in the number of voters who want to vote, providing voting opportunities for people with disabilities, accurate counting of voting results, reducing abuses during the specified process, reducing the time for counting votes, saving money and others. To the problems of their implementation for Ukraine is primarily financial security, in addition, remain a percentage of voters, will not trust such a voting system, and those who will not be ready to use it. Therefore, the use of information technology should be carried out gradually, having prepared for this the appropriate financial, technical, legal, social basis. This study focuses on those electoral procedures, the improvement of the mechanism of implementation of which is a requirement of the time, and Ukraine, as a state with high scientifi c and technical potential, should implement it.
Keywords: electoral procedures; voters; voting; information technologies; electoral lists; registration; polling station